О периодизации и хронологии памятников ранней бронзы - раннего железа на Северо-Восточном Кавказе - Котович, В. Г.
Kotovič, V. G. - Davudov, O. M.; On the Periodisation and Chronology of the Late Bronze-Early Iron Age Sites at the North Eastern Caucasus; engl. Résumé.